Seeing light at the end of the tunnel: Positive prospective mental imagery and optimism in depression. (January 2017) - Ji, Julie L.; Holmes, Emily A.; Blackwell, Simon E.
Abstract: Optimism is associated with positive outcomes across many health domains, from cardiovascular disease to depression. However, we know little about cognitive processes underlying optimism in psychopathology. The present study tested whether the ability to vividly imagine positive events in one's future was associated with dispositional optimism in a sample of depressed adults. Cross-sectional and longitudinal analyses were conducted, using baseline (all participants, N =150) and follow-up data (participants in the control condition only, N =63) from a clinical trial (Blackwell et al., 2015 ). Vividness of positive prospective imagery, assessed on a laboratory-administered task at baseline, was significantly associated with both current optimism levels at baseline and future (seven months later) optimism levels, including when controlling for potential confounds. Even when depressed, those individuals able to envision a brighter future were more optimistic, and regained optimism more quickly over time, than those less able to do so at baseline. Strategies to increase the vividness of positive prospective imagery may aid development of mental health interventions to boost optimism. Highlights: We examined the relationship between positive future imagery vividness and optimism. We analyzed cross-sectional and longitudinal data from a sample of depressed adults. Greater vividness of positive imagery was associated with greater current optimism at baseline. Greater vividness of positive imagery at baseline also predicted greater optimism seven months later. Positive mental imagery may be a useful target for optimism-focused interventions in mental health.